On the determining and minimizing problems of the duration automata - Vũ Anh, Bùi (Journal of Computer Science and Cybernetics, 2014)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";} --> <!--[endif] --> In the previous papers, we have proposed duration automata model and used the model in optimization [3], schedule problems [4] and in problems of the security area [5]. In this paper, we study problem of determining and minimizing the duration automata. Some additional problems are also considered to show how separate and merge durations on the arcs of the automata without changing accepted languages, remove unreachable states (with and without duration meaning). These problems are applied to solve the main problem: determining and minimizing duration automata. <!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";} --> <!--[endif] -->